Realization of wafer-scale nanogratings with sub-50 nm period through vacancy epitaxy - Qiushi Huang (Nature Portfolio, 2019)
Fabrication of wafer-scale nanogratings for X-ray spectroscopy is difficult especially for very high line densities. The authors use vacancy epitaxy to fabricate sub-50-nm-periodicity gratings, coated with multilayers for efficient operation, for use in ultra-high resolution x-ray spectroscopy.